Cholesterol Induces CD8+ T Cell Exhaustion in the Tumor Microenvironment - Ma, Xingzhe; Bi, Enguang; Lu, Yong; Su, Pan; Huang, Chunjian; Liu, Lintao; Wang, Qiang; Yang, Maojie; Kalady, Matthew F.; Qian, Jianfei; Zhang, Aijun; Gupte, Anisha A.; et al. (Cell metabolism, 2019)
Tumor-infiltrating T cells often lose their effector function; however, the mechanisms are incompletely understood. We report that cholesterol in the tumor microenvironment induces CD8+ T cell expression of immune checkpoints and exhaustion. Tumor tissues enriched with cholesterol and cholesterol content in tumor-infiltrating CD8+ T cells were positively and progressively associated with upregulated T cell expression of PD-1, 2B4, TIM-3, and LAG-3. Adoptively transferred CD8+ T cells acquired cholesterol, expressed high levels of immune checkpoints, and became exhausted upon entering a tumor. Tumor culture supernatant or cholesterol induced immune checkpoint expression by increasing endoplasmic reticulum (ER) stress in CD8+ T cells. Consequently, the ER stress sensor XBP1 was activated and regulated PD-1 and 2B4 transcription. Inhibiting XBP1 or reducing cholesterol in CD8+ T cells effectively restored antitumor activity. This study reveals a mechanism underlying T cell exhaustion and suggests a new strategy for restoring T cell function by reducing cholesterol to enhance T cell-based immunotherapy. [Display omitted] •CD8+ T cell exhaustion is correlated with a high cholesterol level•Tumor microenvironment is enriched with cholesterol•Cholesterol in the tumor microenvironment induces CD8+ T cell exhaustion•ER stress-XBP1 pathway is required for cholesterol-induced CD8+ T cell exhaustion Tumor-infiltrating T cells often lose their effector function. Ma et al. show that cholesterol in the tumor microenvironment induces CD8+ T cell exhaustion in an ER-stress-XBP1-dependent manner. Reducing cholesterol or ER stress enhanced CD8+ T cell antitumor function, highlighting therapeutic avenues to improve T cell-based immunotherapy in the clinic.